Indonesia's Nickel Export to China After the 2020 Ban: Prospects, Challenges, and the Islamic Trade Policy Perspective - Annisa Nurul Hayati (Al-Mustashfa: Jurnal Penelitian Hukum Ekonomi Syariah, 2026)
Indonesia’s raw nickel ore export ban, implemented in January 2020, has reshaped the structure of Indonesia–China nickel trade from raw ore dependence toward processed nickel production and downstream industrialization. Five years after the ban, however, the policy requires not only economic assessment but also normative evaluation, particularly regarding value distribution, foreign capital dominance, environmental harm, and labour protection. This article examines whether Indonesia’s post-ban nickel downstreaming policy aligns with Islamic trade policy principles. Using a qualitative normative approach, the study analyzes secondary data and policy literature through the principles of ‘adl, ta‘awun, prohibition of exploitation, amanah, maslahah, and la dharar. The findings show that the export ban corrected a structurally unequal trade pattern by reducing raw ore exports, encouraging domestic processing, and strengthening Indonesia’s position in the global nickel value chain. The policy also reflects state amanah by seeking to manage strategic mineral resources for public welfare. Nevertheless, the post-ban structure remains ethically incomplete. Chinese-affiliated firms continue to dominate refining capacity, raising concerns over unequal value capture, while environmental degradation and labour issues challenge the principles of maslahah and la dharar. The article concludes that nickel downstreaming is broadly consistent with Islamic trade ethics, but its ethical legitimacy depends on fair ownership structures, stronger environmental governance, labour protection, and equitable benefit-sharing with local communities.